The Association Between Specific Oral Behaviors and the Number of Temporomandibular Disorder Symptoms in the General Population: A Cross-Sectional Study - Tian Y; Tan Y; Yang M; Lv X; Zheng Y; Zhang Q; Sun Y; Wang J; Xiong X (Journal of Pain Research)
Yihong Tian,1,2,* Yanyue Tan,3,* Ming Yang,1 Xiayang Lv,3 Yunhao Zheng,1 Qiang Zhang,4 Yanyu Sun,1 Jun Wang,1,2 Xin Xiong1,2 1State Key Laboratory of Oral Diseases, National Clinical Research Center for Oral Diseases, Chengdu, Sichuan, People’s Republic of China; 2Department of Orthodontics, West China Hospital of Stomatology, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Department of Nursing, West China Hospital of Stomatology, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 4Department of Orthodontics, Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Wang; Xin Xiong, West China Hospital of Stomatology, Sichuan University, No. 14 section 3, Renmin South Road, Chengdu, 610041, People’s Republic of China, Email wangjunv@scu.edu.cn; drxiongxin@scu.edu.cnObjective: This study aimed to thoroughly explore the relationship between individual oral behavior and the differing numbers of temporomandibular disorder (TMD) symptom in the general population.Methods: A total of 565 participants were recruited and completed a questionnaire containing demographic characteristics, eight specific oral behaviors, and five major TMD symptoms (5Ts) checklist. Multivariate linear regression analysis was performed to assess the relationship between individual oral behavior and the number of TMD symptoms, after controlling for confounders.Results: The prevalence of TMD symptoms was up to 38.2% in the general population, with 64.6% of the participants engaging in one or more oral behaviors. Female participants showed a stronger positive association with most oral behaviors than males. Moreover, wake oral behaviors exhibited a higher correlation coefficient value with TMD symptom number than sleep oral behaviors. Among the eight oral behaviors, bruxism in sleep exhibited no significant correlation with the of TMD symptom number (P> 0.05). Seven other specific oral behaviors were significantly correlated with the number of TMD symptoms by multivariate linear regression analysis (P< 0.01). The associations between the seven oral behaviors and TMD symptom number remained significant in sleep posture pressuring jaw (β: 0.165, 95% CI: 0.080– 0.250), bruxism in awake (β: 0.341, 95% CI: 0.132– 0.550), teeth clenching (β: 0.422, 95% CI: 0.264– 0.580), pressing, holding, or touching teeth together (β: 0.282, 95% CI: 0.169– 0.395), holding or tightening muscles without clenching (β: 0.447, 95% CI0.304– 0.589), holding jaw forward or to the side (β: 0.694, 95% CI0.526– 0.861), and holding jaw in rigid or tense position (β: 0.571, 95% CI0.418, 0.724) after adjustment for demographic factors (P< 0.01).Conclusion: There was a positive association between seven specific oral behaviors and TMD symptom number. Individuals with higher frequency of specific oral behaviors are more likely to suffer from more TMD symptoms. Sleep bruxism exhibited no association with TMD symptoms and symptom number.Keywords: oral behaviors, temporomandibular disorders, TMD symptom number, cross-sectional study